Oral Communication Strategies Training: The Case of Pre-Service English Teachers in Indonesia - Aridah Aridah; Weningtyas Parama Iswari; Syamdianita Syamdianita; Noor Rachmawaty (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2021)
Background: Many researches on pre-service English teachers have been carried out in various aspects, from teaching techniques to psychology. However, research on oral communication strategies of pre-service English teachers is still little done. This study delved into the effect of oral communication strategies training on pre-service English teachers’ speaking performance. In addition, it revealed the relationship between gender and types of oral communication strategies. Methodology: This study involved 27 students who joined in Speaking 3 course. The OCSI as the instrument in this study consisted of eight categories of strategies for coping with speaking problems and seven types for dealing with listening problems Findings: Results from descriptive statistics showed that before the training, message reduction mainly was used while social affective and attempt to think in English was the least often employed strategy for resolving speaking difficulties. Meanwhile, after the training, a Non-verbal strategy while speaking was frequently used by the students. Message abandonment became the least used strategy after training was implemented. In dealing with listening problems, before the training, Non-Verbal strategies while listening was mostly used while the least used strategy was getting the gist. After the training, Word oriented became the most often employed technique Meanwhile, strategies for preserving fluency were the least frequently adopted. Conclusion: The MANOVA results of data analysis revealed that female students significantly performed better in speaking English than male students. However, there was no significant difference in Oral Communication Strategy used between male and female students.